Evaluation of the engineer's personnel's role in enhancing the project constructability - Nima, Mekdam A.; Jaafar, Mohd. Saleh; Abdul-Kadir, M. Razali (MCB University Press, 1999)
The engineer's personnel play a prominent role in enhancing the constructability of facilities design, construction and assessment. This paper is based on the constructability concepts identified by the Construction Industry Institute (CII) at Austin, Texas and represents and describes the constructability concepts in relation to the engineer's personnel. It discusses the role of each of them in enhancing constructability of facilities projects. A set of obligations has been concluded as an answer to the question of "How can the engineer's personnel enhance the project constructability?".